Effective therapies in benign pain in case of failure of reflex therapies - Paolo Barbagli; Renza Bollettin (Publiediting, 2021)
The authors examined, among all treated cases of benign pain (3662) from 1982 to the first half of 2006 with reflex therapy method, the cases with unsatisfactory results and with other successive successful treatments. This group is made up of 28 cases (with 25 patients, because in 3 cases the patients had more diseases). Between the 25 patients, 8 improved with surgery, 4 with steroid injections, 2 with chiropraxis and/or "manipulations", 2 with laser therapy, 2 with neuraltherapy of Huneke, and 1 each with acupuncture, auriculotherapy, NSAID, phytotherapy, connectival massage, ultrasounds and TENS plus ultrasounds. In conclusion, there is not an only therapy always successful, when a reflex therapy is ineffective, but the therapheutic options can be numerous. Sometimes, the surgical option can therefore be effective; sometimes (3 in this study) it can be effective to change reflex therapy (for example from acupuncture to neural therapy and vice versa).